PCR-Based Techniques for Leprosy Diagnosis: From the Laboratory to the Clinic - Martinez, Alejandra Nóbrega; Talhari, Carolina; Moraes, Milton Ozório; Talhari, Sinésio (PLoS neglected tropical diseases, 2014)
In leprosy, classic diagnostic tools based on bacillary counts and histopathology have been facing hurdles, especially in distinguishing latent infection from active disease and diagnosing paucibacillary clinical forms. Serological tests and IFN-gamma releasing assays (IGRA) that employ humoral and cellular immune parameters, respectively, are also being used, but recent results indicate that quantitative PCR (qPCR) is a key technique due to its higher sensitivity and specificity. In fact, advances concerning the structure and function of the Mycobacterium leprae genome led to the development of specific PCR-based gene amplification assays for leprosy diagnosis and monitoring of household contacts. Also, based on the validation of point-of-care technologies for M. tuberculosis DNA detection, it is clear that the same advantages of rapid DNA detection could be observed in respect to leprosy. So far, PCR has proven useful in the determination of transmission routes, M. leprae viability, and drug resistance in leprosy. However, PCR has been ascertained to be especially valuable in diagnosing difficult cases like pure neural leprosy (PNL), paucibacillary (PB), and patients with atypical clinical presentation and histopathological features compatible with leprosy. Also, the detection of M. leprae DNA in different samples of the household contacts of leprosy patients is very promising. Although a positive PCR result is not sufficient to establish a causal relationship with disease outcome, quantitation provided by qPCR is clearly capable of indicating increased risk of developing the disease and could alert clinicians to follow these contacts more closely or even define rules for chemoprophylaxis.